Westminster dictionary of theological terms - McKim, Donald K. (Louisville, KY Westminster John Knox Press, 1996)
This unique volume briefly identifies nearly six thousand theological terms. Its concise definitions capture a broad range of theological disciplines: biblical studies; church history; ethics; feminist theology; liberation theology; ministry; philosophy; Protestant, Reformed, and Roman Catholic theologies; and more. No other single volume...
Keywords: Theology -- Dictionaries. Théologie -- Dictionnaires anglais. Theology